Letter (copy) : Spain - Citrine, Walter, 1887-1983
022_0013-001 WMC/WJB/AC/571 International 18th March, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, SPAIN. My attention has been drawn to the issue of "Humanité" for 16th March, 1937, in which there appears an article written by Mr. Henri Raynaud, Secretary of the Union des syndicats de la R.P., who attended the joint International Conference last week. The article is of a distinctly tendencious nature, and constitutes a breach of faith, as it was understood that these meetings should be of a private nature, in order that there might be a full and open discussion and a frank exchange of views. If, however, whenever we hold these conferences, any understanding we enter into beforehand is to be ignored for certain party purposes, we shall have seriously to consider whether some other more reliable methods of consultation cannot be adopted. As to the references contained in the article with respect to the British delegation, our action is based on the definite policy of the British Trade Union and Labour Movement. We are, of course, completely indifferent to criticism that is derived from an illusory comprehension of facts, but I think Mr. Raynaud should be made to understand the disservice he is (probably unconsciously) doing to the cause of the Spanish workers, and I have written to Comrade Jouhaux to this effect. I am enclosing a copy herewith. Yours faithfully, General Secretary. Copy of letter to Mr. Jouhaux. 292/946/22/12